Manual control of catalytic reactions: Reactions by an apoenzyme gel and a cofactor gel - Kobayashi, Yuichiro (Sci Rep, 2015)
Enzymes play a vital role in catalysing almost all chemical reactions that occur in biological systems. Some enzymes must form complexes with non-protein molecules called cofactors to express catalytic activities. Although the control of catalytic reactions via apoenzyme–cofactor complexes has attracted significant attention, the reports have been limited to the microscale. Here, we report a system to express catalytic activity by adhesion of an apoenzyme gel and a cofactor gel. The apoenzyme and cofactor gels act as catalysts when they form a gel assembly, but they lose catalytic ability upon manual dissociation. We successfully construct a system with switchable catalytic activity via adhesion and separation of the apoenzyme gel with the cofactor gel. We expect that this methodology can be applied to regulate the functional activities of enzymes that bear cofactors in their active sites, such as the oxygen transport of haemoglobin or myoglobin and the electron transport of cytochromes.